2014
DOI: 10.1371/journal.pone.0097173
|View full text |Cite
|
Sign up to set email alerts
|

ADC Histograms from Routine DWI for Longitudinal Studies in Cerebral Small Vessel Disease: A Field Study in CADASIL

Abstract: Diffusion tensor imaging (DTI) histogram metrics are correlated with clinical parameters in cerebral small vessel diseases (cSVD). Whether ADC histogram parameters derived from simple diffusion weighted imaging (DWI) can provide relevant markers for long term studies of cSVD remains unknown. CADASIL patients were evaluated by DWI and DTI in a large cohort study overa6-year period. ADC histogram parameters were compared to those derived from mean diffusivity (MD) histograms in 280 patients using intra-class cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…Furthermore, it has already been suggested that DTI parameters in general and MD histogram metrics in particular are largely reproducible across different scanners and sequences. Although we cannot fully exclude an influence of scanner type, field strength, and different software versions on MD values, our interscanner reproducibility study using 2 scanners with different field strengths showed the best reproducibility for PSMD. It is plausible that PSMD is less prone to interscanner and interstudy differences than other DTI (histogram) parameters, because peak width does not depend on absolute MD values but rather on the distribution pattern of the histogram.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, it has already been suggested that DTI parameters in general and MD histogram metrics in particular are largely reproducible across different scanners and sequences. Although we cannot fully exclude an influence of scanner type, field strength, and different software versions on MD values, our interscanner reproducibility study using 2 scanners with different field strengths showed the best reproducibility for PSMD. It is plausible that PSMD is less prone to interscanner and interstudy differences than other DTI (histogram) parameters, because peak width does not depend on absolute MD values but rather on the distribution pattern of the histogram.…”
Section: Discussionmentioning
confidence: 65%
“…ROI and histogram analyses of DWI and DTI, which have been employed in previous diffusion‐MRI studies of CADASIL, are characterized by intrinsic limitations. For instance, ROI analysis is biased by a priori selection of a limited number of regions under study, and may suffer from not negligible intra‐ and interoperator variability when ROIs are manually placed .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, using regions of interest (ROI) or histogram analyses, increase of the apparent diffusion coefficient (ADC) or of the mean diffusivity (MD) and decrease of the fractional anisotropy (FA) were observed in CADASIL as compared to healthy controls. Also, histogram measurements of diffusion indices were capable to detect progression of microstructural changes and were recommended for longitudinal studies …”
Section: Introductionmentioning
confidence: 99%
“…By contrast, diffusion tensor tractography (DTT), which is derived from diffusion tensor imaging (DTI), has enabled three-dimensional visualization and estimation of the neural tracts. Since the introduction of DTI, several DTI studies have reported on the usefulness of DTI for detection of lesions of CADASIL [ 4 8 ]. However, no study on neural tract injury in patients with CADASIL has been reported so far.…”
Section: Introductionmentioning
confidence: 99%